Porotic hyperostosis and cribra orbitalia in human remains from southern Patagonia - Suby, Jorge Alejandro (2014)
Previous studies revealed a high frequency of porotic hyperostosis in hunter-gatherer populations from southern Patagonia. Nevertheless, the systematic recovery of new burials with detailed archaeological and paleodietary contextual information during the last two decades offers new opportunities to explore the prevalence of anemia and its possible variation among populations with different marine and terrestrial hunter-gatherer lifestyles. This paper reports the results of an analysis of porotic hyperostosis and cribra orbitalia in skeletal human remains from this region, discussing their most likely causes in the light of current evidence. The results showed a high prevalence of porotic hyperostosis and a low prevalence of cribra orbitalia, without significant differences between age and sexes. Moreover, marine hunter-gatherers presented a higher frequency of porotic hyperostosis than those individuals associated with terrestrial economies. Nutritional and zoonotic factors are proposed as the most probable causes of the high frequency of anemia observed in individuals with marine-based diets. Although no temporal differences were observed, different possible patterns of health in human native populations in the during-contact period are proposed.